Mechanisms of Axon Elongation Following CNS Injury: What Is Happening at the Axon Tip? - Rodemer, William; Gallo, Gianluca; Selzer, Michael E. (Frontiers in Cellular Neuroscience, 2020)
After injury to the central nervous system (CNS), functional recovery is limited by the inability of severed axons to regenerate and form functional connections with appropriate target neurons beyond the injury. Despite tremendous advances in our understanding of the mechanisms of axon growth, and of the inhibitory factors in the injured CNS that prevent it, disappointingly little progress has been made in restoring function to human patients with CNS injuries, such as spinal cord injury (SCI), through regenerative therapies. Clearly, the large number of overlapping neuron-intrinsic and -extrinsic growth-inhibitory factors attenuates the benefit of neutralizing any one target. More daunting is the distances human axons would have to regenerate in order to reach some threshold number of target neurons, e.g., those that occupy one complete spinal segment, compared to the distances required in most experimental models, such as mice and rats. However, the difficulties inherent in studying mechanisms of axon regeneration in the mature CNS in vivo have caused researchers to rely heavily on extrapolation from studies of axon regeneration in peripheral nerve, or of growth cone-mediated axon development in vitro and in vivo. Unfortunately, evidence from several animal models, including the transected lamprey spinal cord, has suggested important differences between regeneration of mature CNS axons and growth of axons in peripheral nerve, or during embryonic development. Specifically, long-distance regeneration of severed axons may not involve the actin-myosin molecular motors that guide embryonic growth cones in developing axons. Rather, non-growth cone-mediated axon elongation may be required to propel injured axons in the mature CNS. If so, it may be necessary to use other experimental models in order to promote regeneration that is sufficient to contact a critical number of target neurons distal to a CNS lesion. This review examines the cytoskeletal underpinnings of axon growth, focusing on the elongating axon tip, in order to gain insights into how CNS axons respond to injury, and how this might affect the development of regenerative therapies for SCI and other CNS injuries.